2017
DOI: 10.1001/jamadermatol.2017.1162
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Tolerance of Anti–Tumor Necrosis Factor α Agents in Cutaneous Sarcoidosis

Abstract: IMPORTANCEEvidence for the long-term efficacy and safety of anti-tumor necrosis factor α agents (anti-TNF) in treating cutaneous sarcoidosis is lacking.OBJECTIVE To determine the efficacy and safety of anti-TNF in treating cutaneous sarcoidosis in a large observational study.DESIGN, SETTING, AND PARTICIPANTS STAT (Sarcoidosis Treated with Anti-TNF) is a French retrospective and prospective multicenter observational database that receives data from teaching hospitals and referral centers, as well as several pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 12 publications
3
30
0
2
Order By: Relevance
“…Der langfristige Einsatz von Glukokortikoiden zur Behandlung von Sarkoidose ist mit erheblichen Nebenwirkungen verbunden, daher ist eine kurzfristige Behandlung nur dann angezeigt, wenn klinische Symptome bestehen bzw. die granulomatöse Entzün-dung rasch fortschreitet [12]. Um folgenschwere Nebenwirkungen von langfristigen Glucokortikoidgaben zu vermeiden, sollte bei einer chronischen Sarkoidose eine Kortison-sparende Therapie erwogen werden.…”
Section: Diskussionunclassified
“…Der langfristige Einsatz von Glukokortikoiden zur Behandlung von Sarkoidose ist mit erheblichen Nebenwirkungen verbunden, daher ist eine kurzfristige Behandlung nur dann angezeigt, wenn klinische Symptome bestehen bzw. die granulomatöse Entzün-dung rasch fortschreitet [12]. Um folgenschwere Nebenwirkungen von langfristigen Glucokortikoidgaben zu vermeiden, sollte bei einer chronischen Sarkoidose eine Kortison-sparende Therapie erwogen werden.…”
Section: Diskussionunclassified
“…Sarcoidosis is a systemic inflammatory disorder wherein the central feature is the formation and propagation of granulomas in affected organs. It has a prevalence of 10 per 100,000 people in the United States, with the incidence and prevalence being higher in African American populations compared to Asians, Hispanics, and Caucasians [ 1 ]. Pulmonary involvement in sarcoidosis is a cardinal feature, however, extra-pulmonary manifestations have been reported in 10-30% of cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] The recent studies reported the rate of cutaneous involvement up to 30% in Germany and about 33% in France. [ 3 , 4 ]…”
Section: Introductionmentioning
confidence: 99%